PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN DI PERGURUAN TINGGI KOTA BALIKPAPAN - Eltimeyansi Crisye Randanan; Esterina Natalia Paindan; Risna Risna (Sekolah Tinggi Teknologi MIGAS, 2019)
Management of hazardous and toxic waste is one of the most important things in handling waste for better nature. Good management can result in a clean water, air and soil environment, good quality of human life and a balanced human future.